Pesticides Are Involved With Population Declines of Amphibians in the California Sierra Nevadas - Donald W. Sparling; Gary Fellers; Laura McConnell (The Scientific World Journal)
Several species of frogs and toads are in serious decline in the Sierra Nevada Mountains of California. These species include the threatened red-legged frog (Rana aurora), foothill yellow-legged frog (R. boylii), mountain yellow-legged frog (R. muscosa), Cascades frog (Rana cascadae), western toad (Bufo boreas) and Yosemite toad (B. canorus). For many of these species current distributions are down to 10% of historical ranges [1,2]. Several factors including introduced predators [3,4,5], habitat loss [2], and ultraviolet radiation [6] have been suggested as causes of these declines. Another probable cause is air-borne pesticides from the Central Valley of California. The Central Valley, especially the San Joaquin Valley, is a major agricultural region where millions of pounds of active ingredient pesticides are applied each year (http://www.cdpr.ca.gov/dprdatabase.htm). Prevailing westerly winds from the Pacific Coast transport these pesticides into the Sierras [7,8].